Fast‐track rehabilitation after robot‐assisted laparoscopic cystectomy accelerates postoperative recovery. (13th November 2012) - Saar, Matthias; Ohlmann, Carsten‐Henning; Siemer, Stefan; Lehmann, Jan; Becker, Frank; Stöckle, Michael; Kamradt, Jörn
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? There is evidence from large abdominal surgeries and some open cystectomy series that multifactorial fast‐track regimens shorten postoperative convalescence without any effect on morbidity and mortality. Such a regimen is of particular interest in combination with minimally invasive techniques, as early patient recovery demands for more rapid nutrition and mobilisation schemes. The present study, in a single institution, reports on the design, application and results of a fast‐track protocol in patients undergoing robot‐assisted laparoscopic cystectomy. There was no evidence of a higher incidence of complications with the fast‐track regimen and postoperative recovery was faster. Objectives To evaluate the feasibility and effectiveness of a multifactorial fast‐track (FT) regimen on perioperative outcomes in patients undergoing robot‐assisted laparoscopic cystectomy (RALC) with extracorporeal urinary diversion. To point out that morbidity and mortality of radical cystectomy have improved markedly over the last decades and RALC is an emerging technique showing further advances in postoperative recovery, thus demanding for more rapid nutrition and mobilisation schemes. Patients and Methods A non‐randomised cohort study of 63 patients who underwent RALC at one institution between January 2007 and March 2010. In all, 31 patients underwent RALC without FT and 31 RALC with FT. One patient required conversion to open surgery and was therefore excluded from the study. The FT regimen included early nutrition and the quickest possible mobilisation, while mechanical bowel preparation before surgery, as well as preoperative fasting and nasogastric or abdominal drains after surgery, were omitted. Demographics, perioperative and complication data (according to modified Clavien system), as well as required opioid pain medication were documented prospectively and compared between RALC patients with and without FT. Results Groups were comparable for demographics, risk factors and clinical stage as well as operative parameters, e.g. mean operating room time, estimated blood loss, lymph nodes removed and postoperative haemoglobin level. In the FT group, abdominal drains were mostly omitted and nasogastric tubes were removed immediately after surgery. There were significant differences in the mobilisation within the room (17.5 vs 31.2 h), the time to a regular diet (4.0 vs 6.6 days) and a remarkably lower use of postoperative morphine equivalents (57.3 vs 92.4 mg) for patients receiving FT. There were no significant differences in the overall complication rates or major complications based on Clavien classification. The informative value of the study is limited by its single‐centre, non‐randomised design, a relatively small sample size and a possible learning curve bias. Conclusions Combining RALC with FT is feasible in the perioperative treatment of these patients. Multifactorial postoperative regimens seem to quicken postoperative recovery of RALC patients without increasing their risk of postoperative complications.